The study of cervical cancer screening using pap test and correlation with high-risk genotypes (Journal of Pathology of Nepal, 2025)
Background: Cervical cancer is a significant health concern in India, and early detection is crucial. This study aimed to evaluate the prevalence and genotype of human papillomavirus in abnormal pap smears and correlate findings with histopathology.Methods and Materials: A one-year prospective study was done at Santosh Medical College, screening 3194 cases. HPV testing was performed on all patients, and biopsies were taken from those with abnormal epithelial lesions. The study includes sexually active women or women presenting with complaints such as abdominal pain, abnormal vaginal discharge or bleeding, or other vaginal sensations. It excludes unsatisfactory smears, unmarried females, pregnant women, lactating women, and diagnosed or treated cases of cervical carcinoma.Conclusions: This study suggests that pap and HPV co-testing from the initial visit can be cost-effective and reduce the need for follow-up appointments.